Current Approaches to Ulcerative Colitis Management: A Comprehensive Overview of Methodologies and Treatments - Rawat, Aman; Srivastava, Richa (Infectious Disorders - Drug Targets, 2025)
Ulcerative colitis is a chronic, idiopathic, inflammatory condition affecting the colon, primarily impacting individuals aged 30 to 40. It typically begins in the rectum and gradually progresses to the proximal regions of the colon, characterized by recurrent and remitting mucosal inflammation. Ulcerative colitis is categorized under inflammatory bowel disease, which encompasses various gastrointestinal tract disorders, but its underlying pathophysiology remains unclear. The development of ulcerative colitis is influenced by a combination of genetic, environmental, and inflammatory factors. The severity of the disease guides the management of ulcerative colitis. Restorative strategies include the use of TNF-α (anti-tumor necrosis factor-alpha) monoclonal antibodies. Janus Kinase inhibitors suppress cell signaling of the innate immune system. As ongoing research continues, the treatment options for ulcerative colitis are continually evolving and improving. Various types of dosage forms (tablets, capsules, suppositories, etc.) are available in the market for managing ulcerative colitis, with the primary goal of achieving and maintaining clinical and endoscopic remission of the disease. Ensuring a high level of patient compliance is crucial when considering the formulation of these dosage forms. This review article seeks to offer a comprehensive understanding of ulcerative colitis while highlighting the existing treatment options on various available dosage forms.
Keywords: suppositories